1980
DOI: 10.1128/aem.39.4.900-907.1980
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylamide Slab Gel Electrophoresis of Soluble Proteins for Studies of Bacterial Floras

Abstract: A polyacrylamide slab gel electrophoresis procedure was used to compare cellular proteins from bacterial isolates of gingival crevice floras. Isolates with identical protein patterns consistently were shown to be members of the same species. When used to screen isolates, the procedure reduced total analytical time and expense without sacrificing accuracy, and it provided additional verification of the identity of strains characterized by conventional phenotypic tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(64 citation statements)
references
References 17 publications
(22 reference statements)
0
64
0
Order By: Relevance
“…Although Moore et al (1985) did not uniformly sample progressive periodontal lesions to represent disease, they also found that W. recta and B. gracilis were related to diseased sites. Moore et al (1985) found W. curva and C. concisus were related to diseased sites. In this investigation, we did not identify W. curva from deep periodontal sites and few C. concisus strains were isolated.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although Moore et al (1985) did not uniformly sample progressive periodontal lesions to represent disease, they also found that W. recta and B. gracilis were related to diseased sites. Moore et al (1985) found W. curva and C. concisus were related to diseased sites. In this investigation, we did not identify W. curva from deep periodontal sites and few C. concisus strains were isolated.…”
Section: Discussionmentioning
confidence: 92%
“…It is of interest that B. gracilis is isolated with increasing frequency from deep extra-oral infections (Johnson, Reinhardt & Finegold 1985). Although Moore et al (1985) did not uniformly sample progressive periodontal lesions to represent disease, they also found that W. recta and B. gracilis were related to diseased sites. Moore et al (1985) found W. curva and C. concisus were related to diseased sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also Moore etal. (13) and Tanner (29) have differentiated oral bacteria by PAGE of cellular proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Gram-positive cocci are among the most difficult bacteria to disrupt by physical methods (Dobrogosz 1981). Shaking staphylococci with glass beads potentially gives small scale, highly variable extraction (Moore et a!. 1980).…”
mentioning
confidence: 99%